Robert, University of Pennsylvania Radiocarbon Dates, VI - Stuckenrath, Jr. (1963)
82-83: Syria: Ras Shamra; 84-85: Iraq: Grai Resh, Nimrud, Nippur; 85-92: Iran: Hasanlu Tepe, Pisdeli Tepe, Dalma Tepe, Hajji Firuz Tepe, Tall-i-Bakun, Yarim Tepe, Tepe Siahbid, Tepe Sarab; 92-93: India: Kalibangan; 93-94: West Pakistan: Kile Gul Mohammad, Niai Buthi, Damb Sadaat.